Industrial production management in flexible manufacturing systems - Dima, Ioan Constantin, 1956- (Engineering Science Reference, 2013)
"This book addresses the present discussions surrounding flexible production systems based on automation, robotics and cybernetics as they continue to replace the traditional production systems"--Resumé vydavatele
Premier reference source"--Z obálky
Keywords: výrobní management; výrobní systémy; operační management; production management; manufacturing systems; operations management; monografie; monographs